Exploring how multimorbidity care is managed for an older Irish patient population within clinician networks: Preliminary findings from an SNA survey - Lee, Mandy; Normand, Charles; Caffrey, Orla (My University, 2017)
Studies focusing on managing care for people with multimorbidity show: – Health Service Utilisation: Long-term Use; Multiple Services at Same Time; Community Dwelling Ageing Cohort – Health Service Integration: Difficulty in continuity of care due to “Disease Silos” – Complexity of Care Management: 43% of Multimorbidity Complexity came from challenges associated with coordinating care as opposed to clinical complexity. (Blay, 2016) Type of Multimorbidity Care Being Promoted – Self-managed Care with help from Community & Family Support – Seamless Continuity of Care Between Primary & Secondary Care – More Care to Take Place in the Community
Third European Conference on Social Networks
Keywords: Ageing; AGEING; multimorbidity